PENGARUH WORD OF MOUTH DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA MAWAR BAKERY & CAKE SHOP STUDI KASUS DI KOTA MEDAN - Damanik, Lisa Gresti Sella; Mangopo, Yuni Riskita; Landjang, Xenia Irene Sandy; Toii, Indra Eka Wardana (Gapenas Publisher, 2025)
This research aims to determine the influence of word of mouth and product quality on purchasing decisions at Mawar Bakery & Cake Shop, a case study in Medan City. The method used is quantitative. The population in this study is consumers of Mawar Bakery & Cake Shop in Medan City, totaling 206 people. The sampling technique used is probability sampling, and the sample collection method uses the Slovin formula. The research sample consists of 135 respondents. The data obtained were analyzed using the Structural Equation Model Partial Least Square (PLS) technique. The results of the study indicate that the word-of-mouth variable has a positive and significant effect on purchasing decisions, with the path coefficient value showing a T-Statistic value of 4.595 with a P-Value of 0.000 and an original sample value of 0.402. Thus, the T-Statistic value is greater than the T-table (1.97). Product quality has a positive and significant effect on purchasing decisions, with a T-Statistic value of 4.426 with a P-Value of 0.000 and an original sample value of 0.385. Thus, the T-Statistic value is greater than the T-table (1.97). The location of the business has an influence on purchasing decisions, therefore it is recommended that the owner of Mawar Bakery & Cake Shop, in determining the location of the business, can pay attention to environmental factors around the business location such as the condition of the community around the business location, the comfort and safety of the business place, and easy access for buyers. The results showed that there are still other factors that can affect purchasing decisions besides word of mouth and product quality, therefore it is recommended that the owners of Mawar Bakery & Cake Shop conduct a survey directly to buyers regarding the assessment of consumer satisfaction with word of mouth and product quality based on buyers' perceptions so that owners of Mawar Bakery & Cake Shop can make strategies to improve their business according to the characteristics of buyers who are their target market.